Does activity mix and funding strategy vary across ownership? Evidence from Indian banks - Saibal Ghosh (Atlantic Review of Economics, 2011)
Using data on Indian banks during 1996-2007, the paper examines the impact of bank activity and short-term funding for bank returns and risks. The findings indicate that larger, fast growing financial firms tend to have higher fee income shares. In addition, banks with greater reliance on fee income generating activities exhibit higher profitability. On the contrary, the impact of non-deposit funding share on bank profitability is weak. In terms of bank riskiness, the evidence is consistent with the conjecture that big, cost efficient and capitalized banks are less risky. As in case of bank profitability, there is limited evidence on any non-linear relationship between risk and fee incomes as also between risk and non-deposit funding share. Finally, the analysis supports the fact that foreign and de novo private banks exhibit lower risk as compared to old private banks.
Keywords: G21; G28; P52; 330; banking; return on asset; Z-score; fee income; non-deposit funding; India; Bankgeschäft; Rentabilität; Refinanzierung; Indien